Analysis of Students' Critical Thinking Skills in Solving Ethnomathematics Problems - Eric Dwi Putra; Ahmad Maulana Akbar (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
Mathematics has an important role in the development of critical and logical thinking skills. However, the results of the PISA survey show that the mathematical literacy of students in Indonesia is still low. One approach that can be applied to improve critical thinking skills in mathematics learning is ethnomathematics. Ethnomathematics connects mathematical concepts with cultural elements, thus making learning more contextual and engaging. This study aims to analyze students' critical thinking skills in solving ethnomathematics problems. Based on the results of observations and interviews, it was found that most students still tend to memorize without understanding or critically analyzing information. The implementation of ethnomathematics in learning is expected to help students understand that mathematics is not only abstract but also related to daily life and culture. This study highlights the importance of the application of ethnomathematics in improving mathematical literacy and critical thinking of students, by taking the example of a tobacco warehouse in Jember Regency as one of the cultural objects that can be integrated in mathematics learning.